Parameatal urethral cyst of glans penis in children - a report of three cases - Mrinal Gupta; Anish Gupta (Our Dermatology Online, 2015)
Parameatal urethral cysts are a rare benign condition usually seen in males. They are usually asymptomatic but may produce symptoms like difficulty in micturition, pain during intercourse, urinary retention and distortion of the urinary stream. We report three cases of parameatal urethral cyst in young males presenting as a spherical clear fluid filled cystic lesions over the external urethral meatus, causing distortion of the urinary stream and poor cosmesis. Histological examination of the excised cyst showed a monolocular cyst lined with pseudo-stratified epithelium with no evidence of inflammation. Complete surgical excision of the cysts was done and no recurrence was observed at follow-up.